Association of vegetarian diet with inflammatory biomarkers: a systematic review and meta-analysis of observational studies. Issue 15 (24th August 2017) - Haghighatdoost, Fahimeh; Bellissimo, Nick; Totosy de Zepetnek, Julia O; Rouhani, Mohammad Hossein
Abstract: Objective: Vegetarian diets contain various anti-inflammatory components. We aimed to investigate the effects of vegetarianism on inflammatory biomarkers when compared with omnivores. Design: Systematic review and meta-analysis. Setting: Literature search was conducted in Science Direct, Proquest, MEDLINE and Google Scholar up to June 2016. Summary estimates and corresponding 95 % CI were derived via the DerSimonian and Laird method using random effects, subgroup analyses were run to find the source of heterogeneity and a fixed-effect model examined between-subgroup heterogeneity. Subjects: Studies were included if they evaluated effects of any type of vegetarianism compared with omnivores on circulating levels of inflammatory biomarkers. No restriction was made in terms of language or the date of study publications. Results: Eighteen articles were included. Pooled effect size showed no difference in high-sensitivity C-reactive protein (hs-CRP) levels in vegetarians v . omnivores (Hedges' g =−0·15; 95 % CI −0·35, 0·05), with high heterogeneity ( I 2 =75·6 %, P <0·01). A subgroup analysis by minimum duration of vegetarianism showed that a minimum duration of 2 years vegetarianism was associated with lower hs-CRP levels v . omnivores (Hedges' g =−0·29; 95 % CI −0·59, 0·01), with moderate heterogeneity ( I 2 =68·9 %, P <0·01). No significant effect was found in studies using a minimum duration of 6 months of vegetarianism, with low heterogeneity. Vegetarianism was associated with increased IL-6 concentrations (0·21 pg/ml; 95 % CI 0·18, 0·25), with no heterogeneity ( I 2 =0·0 %, P =0·60). Conclusions: The meta-analysis provides evidence that vegetarianism is associated with lower serum concentrations of hs-CRP when individuals follow a vegetarian diet for at least 2 years. Further research is necessary to draw appropriate conclusions regarding potential associations between vegetarianism and IL-6 levels. A vegetarian diet might be a useful approach to manage inflammaging in the long term.